Incidental Archaeologists : French Officers and the Rediscovery of Roman North Africa - Effros, Bonnie (Cornell University Press, 2018)
In Incidental Archaeologists, Bonnie Effros examines the archaeological contributions of nineteenth-century French military officers, who, raised on classical accounts of warfare and often trained as cartographers, developed an interest in the Roman